"We aren't looking at this as an audition" : exploring interim leadership in college athletics - Browning, Blair; Kassing, Jeffrey W. (London : Human Kinetics, Inc., 2011)
Interim coaches have become commonplace in college athletics. With much at stake, they must act as leaders despite the constraints that accompany interim status. This case study provides an initial examination of interim leadership in the domain of college athletics by focusing on a specific high-profile interim coach's initial press conference. The authors specifically consider the content of The Ohio State University football coach Luke Fickell's first press conference after being named interim head coach. Their analysis reveals that Fickell strategically managed the interim label and the temporal nature of the interim role, balanced service goals and career-aspirant ones, and performed collective identity through a variety of means. The implications of these practices for interim coaches in college athletics are discussed.
Originally published in Browning, B. W., & Kassing, J. W. (2011). "We aren't looking at this as an audition": Exploring interim leadership in college athletics. International Journal of Sport Communication, 4(4), 514-528. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Fickell, Luke; Ohio State University -- Football; College sports -- Coaching; Sports administration; Interim executives